Correlation of oxidative stress with vitamin D and glycated hemoglobin in patients with type 2 diabetes mellitus. Issue 1 (2nd January 2023) - Mehta, Aryan; Bansal, Radha; Kaur, Sukhraj
Abstract: Type 2 diabetes mellitus (T2DM) has a heavy disease burden and is one of the leading causes of death worldwide. It is considered to be evolving from a complex and multifactorial metabolic disorder to an inflammatory condition. The strong link between hyperglycemia and oxidative stress has long been established. Oxidative stress leads to the generation of inflammatory mediators and reactive oxygen species, which results in an inflammatory state, which plays a key role in the pathogenesis of diabetic complications. Vitamin D is also known to affect insulin sensitivity. We aimed to correlate the levels of glycated hemoglobin (HbA1c) and vitamin D with oxidative stress. This cross-sectional study included 100 patients with T2DM. Oxidative stress was estimated by lipid peroxidation assay for activity of malondialdehyde (MDA), as well as superoxide dismutase (SOD) levels. HbA1c was estimated using ion-exchange chromatography. Vitamin D was estimated using enzyme-linked immunosorbent assay. The data were analyzed using a t test. The results showed that as the duration of T2DM increased, the levels of SOD and MDA also increased. No significant correlation was found between SOD and MDA with HbA1c ( P = 0.995 and 0.195) and vitamin D ( P = 0.874 and 0.051), respectively.